Counter-essentialist femininity in post-dictatorship Argentine dramaturgy—A comparative study in Northwestern and Patagonian regions - Tossi, Mauricio (Íkala, Revista de Lenguaje y Cultura, 2019)
During the dictatorial periods, Argentine dramaturgy consolidated a specific identity rhetoric, which was represented aesthetically and imaginatively through the “feminized nation”. This essentialist figuration was the object of speeches pronounced by the dictators, and by the opponents of authoritarian regimes. The purpose of this article is to analyze the hermeneutic revival of this imaginary figuration on women in the postdictatorial dramaturgies of the Argentinean Patagonia and Northwestern Argentina, in order to understand their particular poetic procedures and their counter-essentialist identitarian positions. In line with this, we will use theoretical-methodological tools from the anthropology of the imaginary (Wunenburger, 2008), the sociology of culture (Proaño-Gómez, 2002; Grimson, 2012) and comparative literature (Palermo, 2005; Dubatti, 2008).